Collective synchrony increases prosociality towards non‐performers and outgroup members. (29th September 2016) - Reddish, Paul; Tong, Eddie M. W.; Jong, Jonathan; Lanman, Jonathan A.; Whitehouse, Harvey
Abstract : Previous research has found that behavioural synchrony between people leads to greater prosocial tendencies towards co‐performers. In this study, we investigated the scope of this prosocial effect: does it extend beyond the performance group to an extended ingroup ( extended parochial prosociality ) or even to other people in general ( generalized prosociality )? Participants performed a simple rhythmic movement either in time (synchrony condition) or out of time (asynchrony condition) with each other. Before and during the rhythmic movement, participants were exposed to a prime that made salient an extended ingroup identity. After the task, half of the participants had the opportunity to help an extended ingroup member; the other half had the opportunity to help an outgroup member. We found a main effect of our synchrony manipulation across both help targets suggesting that the prosocial effects of synchrony extend to non‐performers. Furthermore, there was a significantly higher proportion of participants willing to help an outgroup member after moving collectively in synchrony. This study shows that under certain intergroup contexts synchrony can lead to generalized prosociality with performers displaying greater prosociality even towards outgroup members.